2018
DOI: 10.1515/jpem-2018-0148
|View full text |Cite
|
Sign up to set email alerts
|

Single center experience of biotinidase deficiency: 259 patients and six novel mutations

Abstract: Background Biotinidase deficiency (BD) is an autosomal recessively inherited disorder of biotin recycling. It is classified into two levels based on the biotinidase enzyme activity: partial deficiency (10%-30% enzyme activity) and profound deficiency (0%-10% enzyme activity). The aims of this study were to evaluate our patients with BD, identify the spectrum of biotinidase (BTD) gene mutations in Turkish patients and to determine the clinical and laboratory findings of our patients and their follow-up period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 31 publications
2
43
3
3
Order By: Relevance
“…From our data, a remarkable overall incidence of 1:5,996 newborns with BD, combining partial and total deficiencies, emerged. Our incidence is significantly higher than previously reported in literature (5), even if recently some authors reported case studies identified by NBS with comparable incidences in different countries (2,3,13,21).…”
Section: Discussioncontrasting
confidence: 62%
“…From our data, a remarkable overall incidence of 1:5,996 newborns with BD, combining partial and total deficiencies, emerged. Our incidence is significantly higher than previously reported in literature (5), even if recently some authors reported case studies identified by NBS with comparable incidences in different countries (2,3,13,21).…”
Section: Discussioncontrasting
confidence: 62%
“…Aile taramasında (Şekil 2) klinik olarak belirtiye sahip olmayan erkek kardeşinde de (III-5) biyotinidaz eksikliği ile uyumlu p.Asp444His, p.Ala171Thr mutasyonları saptandı. İki mutasyon taşıdığı halde asemptomatik olan benzer hastalar daha önce bildirilmiştir (2). Stresli dönemlerde saç dökülmesi, tırnak kırılması, dematit gibi ılımlı semptomlar tarifleyen annesi (II-8) ve kız kardeşlerinde (III-3 ve III-4) ise BTD geni mutasyonu saptanmadı.…”
Section: Tablo 1 Hastaların Geliş Nedeni Ve Dizi Analizi Sonuçlarıunclassified
“…Biyotin, dört karboksilaza (piruvat karboksilaz, propionil-CoA karboksilaz, metilkrotonil-CoA karboksilaz ve asetil-CoA karboksilaz) kovalent bağlanarak koenzim fonksiyonu gören suda çözünen bir vitamindir. Bu enzimler glukoneogenez, yağ asidi sentezi ve amino asit katabolizmasında rol alırlar (1,2). Biyotinidaz, biyotinin diyet proteinlerinden serbest bırakılarak emilmesinde ve aktif holokarboksilazlar gibi biotinil peptidlerden serbest bırakılarak yeniden biyotin döngüsüne katılmasında kritik bir rol oynayan enzimdir.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Biotin supplementation in a dose ranging from 10 to 20 mg/d can improve the clinical picture, especially if started early. 12 Recurrent subacute encephalopathy is one of the importance early features of biotin-thiamine-responsive basal ganglia disease. It is an increasingly recognized condition and can lead to coma and death if not promptly treated.…”
mentioning
confidence: 99%